“Legal Consciousness” in Adam Podgórecki’s Sociological Theory of Law - Naoumowa, Stefka (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
The issue of legal consciousness occupies a central place in the sociology of law and is of particular relevance for socio-legal knowledge. Prof. Adam Podgórecki has great merit not only in determining the subject of the sociology of law, and the structure of the socio-legal knowledge, but also in delineating the importance of the legal consciousness as a research problem. The article addresses the problem of legal consciousness in the works of A. Podgórecki. In his view, in order to answer a question that is fundamentally important for jurisprudence, and to understand the ramifications of the operation of law in society, it is necessary to study not only the external manifestations of law (the behaviour of its actors and agents) but also the internal (or internalised) dimension of legal phenomena. The structure of legal consciousness includes three main elements, to which the empirical socio-legal analysis is most often directed; the knowledge of legal regulations in force, the evaluation of obligatory laws, and postulates related to what may be defined as good or desirable law. A. Podgórecki examines legal consciousness in the context of several important problems of law in the sociological sense of the word, which is also the core of his sociological theory of law. These include the relationship between intuitive law (“legal sense”) and official law; the relationship between law and morality; effective operation of the law; identification of pathologies of the law; attitudes to the law and to the actual behaviour regulated by law. The most important pieces of empirical research carried out by A. Podgórecki are presented in the article.